Age-related increase in GABAA receptor distribution in the prefrontal cortex. (June 2019) - Tobinaga, Masanobu; Suzuki, Yuji; Fujinaka, Hidehiko; Ozawa, Tetsuo; Nakajima, Takashi
Highlights: There are few reports on age-related changes in the cerebral GABAA-R distribution. We examined the age-related changes in the prefrontal cortex for normal subjects. GABAA-R distribution in the PFC increases within the age range of 20–60 years. Age-related changes should be considered for accurate assessment of GABAA-R. Abstract: Profound insight into age-related changes in γ-aminobutyric acid type A receptor (GABAA-R) distribution using iodine-123-iomazenil single photon emission computed tomography (IMZ-SPECT) can contribute to accurate in vivo evaluation. We evaluated the age-related changes in prefrontal cortex (PFC), which is the key region involved in various neurological and psychiatric diseases. In this study, IMZ-SPECT imaging data of 21 healthy males with an age range of 22–59 (mean, 38 ± 12) years were analyzed using three-dimensional stereotactic surface projection (3D-SSP). The Z-score images of the younger group (age < 40, n = 11) and the older group (age ≥ 40, n = 10) were compared. Subsequently, the mean RI-count ratios calculated for each Brodmann area (BA) by stereotactic extraction estimation method were compared between these groups. Thereafter, linear regression analysis between age and RI-count ratio was performed for all enrolled subjects. In the result, IMZ accumulation increased in bilateral BA10, 11, and the BA47 (left hemisphere) in the older group compared with the younger group. Furthermore, regression analysis demonstrated a significant positive correlation between age and RI-count ratio in these areas. Our findings indicate that GABAA-R distribution in the PFC relatively increases with age. Therefore, we concluded that the age-related changes should be considered to accurately evaluate pathophysiology of neurological and psychiatric diseases.